(3GdUHZ GdbGfhfjI ddEfPQGJ Ydi jO eMVQ habG dbGfhf GdJLGQI Qbe (B17 (3dSfI (B1999 (3hbGfhf MeGjI GdedcjI GdacQjI Qbe (B82 (3dSfI (B2000 /s - (3MSf, Ydj YhVs ((3GdEScfOQjI(B: s (3OGQ GdeWHhYGJ GdLGeYjI(B, s, 2003)
(3GdbGfhf GdeOfj hbGfhf GdeQGaYGJ(B- (3GdbGfhf GdJLGQj hGdHMQj hGdVQGFH(B- (3GdYed hGdJCejfGJ GdELJeGYjI(B- (3GdfbGHGJ GdYeGdjI(B- (3GdCMhGd GdTNUjI(B- (3GdbGfhf GdEOGQj hGdLfGFj(B- (3MGdGJ eJaQbIs
Keywords: (3GdbGfhf GdJLGQjs